Cationic polymer and application thereof in soil improvement

By introducing quaternary ammonium salt into the cellulose framework, adjusting the group ratio, a high degree of substitution quaternary ammonium salt-type cationic cellulose ether was prepared for soil improvement, and the soil water retention and fertilizer retention effects in the prior art were solved. Problem, better soil moisture retention and fertilizer adsorption effect are achieved.

CN119176884APending Publication Date: 2024-12-24HUAQING AGRI DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411341747.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The prior art has not yet met the full demand for soil improvement in cellulose modification, especially in improving the water and fertilizer retention effect of the soil.

Method used

By introducing hydrophobic groups into the cellulose framework, adjusting the ratio of hydrophilic groups and hydrophobic groups, a quaternary ammonium cationic cellulose ether was prepared. As a soil improver, epoxy propyl trioxide was used as a soil modification agent. As an etherifying agent, the molar ratio and reaction conditions are controlled, and the degree of substitution is improved to improve the water and fertilizer retention properties of the soil.

Benefits of technology

It significantly improves the water and fertilizer retention effect of the soil, enhances the soil's moisture retention ability and fertilizer adsorption ability, delays water loss and nutrient loss, and improves the overall productivity of the soil.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119176884A_ABST
    Figure CN119176884A_ABST
Patent Text Reader

Abstract

The invention provides a cationic polymer and application thereof in soil improvement, and belongs to the technical field of soil improvement. The cationic polymer is quaternary ammonium salt type cationic cellulose ether and is prepared according to the following method: (1) adding hydroxypropyl methyl cellulose into a reaction device filled with an alkaline isopropanol solution, stirring until the hydroxypropyl methyl cellulose is completely dissolved, and reacting to obtain a substance A; and (2) adding epoxypropyl triamyl ammonium chloride into the substance A obtained in the step (1), uniformly stirring for reaction, and after the reaction is finished, purifying and drying to obtain the quaternary ammonium salt type cationic cellulose ether. According to the preparation method, epoxypropyl triamyl ammonium chloride is adopted as an etherifying agent, and the molar ratio of reactants is controlled, so that the obtained quaternary ammonium salt type cationic cellulose ether has higher substitution degree; when the quaternary ammonium salt type cationic cellulose ether prepared by the invention is used as a component of a soil conditioner for soil improvement, the water and fertilizer retention effect of soil can be obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of soil improvement, and in particular relates to a cationic polymer and application thereof in soil improvement. Background Art

[0002] With the continuous development of society, soil resources are seriously insufficient, and due to some unreasonable utilization, such as large-scale unreasonable application of fertilizers, excessive spraying of pesticides, over-grazing, etc., the soil has been seriously degraded. The main manifestations are soil compaction and hardening, erosion, salinization, acidification, element imbalance, chemical pollution, organic matter loss and degradation of flora and fauna. The result of soil degradation is reduced soil productivity, reduced crop quality, and even enrichment of toxic elements. Therefore, how to maintain soil quality, improve acid-base soil, eliminate soil toxicity, and reduce the spread of soil-borne diseases has become the focus of people's attention.

[0003] The application of soil conditioners is one of the important measures to repair degraded soil. Soil conditioners can effectively improve the physical and chemical properties of soil and soil nutrient status, and have a positive effect on soil microorganisms, thereby improving the productivity of degraded soil. Soil properties include soil results, soil water content, soil temperature, soil enzyme activity, soil microbial population, soil aeration conditions, soil solution concentration, and soil hydrogen ion concentration. Different types of soil conditioners have different mechanisms of action on the soil, but they all effectively improve the physical structure of the soil, reduce soil bulk density, increase soil water content, change soil chemical properties, increase soil microbial activity, increase enzyme activity, increase soil trace element content, and adjust some or all of the soil water, fertilizer, air, and heat conditions to ultimately achieve the purpose of improving soil fertility.

[0004] Cellulose is abundant in nature and has unique and unparalleled natural advantages. Reasonable research and development of cellulose and its derivatives will be widely used in various industries such as food and sewage treatment. However, due to the presence of a large number of hydroxyl groups in the cellulose structure, van der Waals and strong hydrogen bonding forces are formed between and within molecules, making it essentially insoluble in common solvents, which seriously hinders the development of cellulose-based materials. Therefore, effective separation and extraction of cellulose and modification of cellulose in a uniform environment have become hot topics for cellulose-based materials.

[0005] For example, Chinese patent CN110066201A discloses a conditioner for improving compacted tobacco-growing soil and its preparation method. The conditioner of the invention is prepared by an advanced method, and includes the following components: modified cellulose, modified chitin, snail manure and earthworm manure, wherein the modified cellulose is prepared from peanut shells and fir bark, and the modified chitin is prepared from lobster shells and peanut shells, and the volume ratio of the modified cellulose, modified chitin, snail manure and earthworm manure is 3-5:2-4:1-2:1-2. After using the conditioner of the invention, the soil bulk density is reduced, the total porosity and ventilation porosity are increased, the soil organic matter and total nitrogen content are significantly increased, the microbial activity of tobacco-growing soil is also significantly increased, the compaction of tobacco-growing soil is improved, and the soil permeability is significantly increased.

[0006] For another example, Chinese patent CN118496039A discloses a water-retaining and fertilizing desertified soil improver and a preparation method thereof. The water-retaining and fertilizing desertified soil improver consists of slow-release microspheres loaded with humic acid, a polyacrylic acid resin framework and edible fungus residue; the slow-release microspheres loaded with humic acid consist of modified corn cob cellulose, bentonite, humic acid, sodium alginate and calcium chloride; the slow-release microspheres loaded with humic acid, edible fungus residue and the polyacrylic acid resin framework are cross-linked to prepare the water-retaining and fertilizing desertified soil improver, which has a strong cross-linked network structure, significantly improves the water-retaining and water-holding capacity of the desertified soil, effectively reduces the loss of nutrients, and at the same time improves the aggregate structure in the soil, increases the soil porosity, plays a good role in improving the desertified soil, and has excellent water-retaining and fertilizing properties.

[0007] Although there are many existing technologies for modifying cellulose, they still cannot meet the needs very well. Therefore, it is necessary to further expand the types of modified cellulose so that it has a wider range of applications. Summary of the invention

[0008] Based on the deficiencies of the prior art, the present invention aims to provide a cationic polymer, wherein the cationic polymer is a quaternary ammonium salt type cationic cellulose ether. The present invention introduces a hydrophobic group quaternary ammonium salt into the cellulose skeleton and adjusts the ratio of the hydrophilic group hydroxyl group and the hydrophobic group to obtain a soil conditioner with good water and fertilizer retention effects.

[0009] In order to achieve the above object, the present invention adopts the following technical solution:

[0010] A cationic polymer, wherein the cationic polymer is a quaternary ammonium salt cationic cellulose ether, and is prepared according to the following method:

[0011] (1) adding hydroxypropyl methylcellulose to a reaction device containing an alkaline isopropanol solution, stirring until completely dissolved, and obtaining substance A after reaction;

[0012] (2) adding glycidyltriammonium chloride to the substance A obtained in step (1), stirring the mixture evenly and reacting the mixture; after the reaction is completed, purifying and drying the mixture to obtain the quaternary ammonium salt type cationic cellulose ether.

[0013] The alkaline isopropanol solution in step (1) is a mixed solution of isopropanol-water-sodium hydroxide;

[0014] in,

[0015] The volume fraction of the isopropanol is 30-60%, preferably 40%.

[0016] The molar ratio of sodium hydroxide to hydroxypropyl methylcellulose is 0.30-0.50:1, preferably 0.45:1.

[0017] The above step (1) needs to be carried out under heating conditions, and the heating temperature is 40-50°C, preferably 45°C.

[0018] The reaction time of the above step (1) is 0.5-1.5 hours, preferably 1.2 hours.

[0019] The molar ratio of glycidyl tripentylammonium chloride to hydroxypropyl methylcellulose in the above step (2) is 0.35-0.65:1; preferably 0.4-0.5:1, and more preferably 0.45:1.

[0020] The reaction temperature in the above step (2) is 60-80°C, preferably 65-75°C, and more preferably 70°C.

[0021] The reaction time of step (2) is 5-8 hours, preferably 6-7 hours, and more preferably 7 hours.

[0022] As some preferred embodiments, the epoxypropyl tripentyl ammonium chloride is prepared by the following method:

[0023] Potassium sulfate crystals, water, anhydrous ethanol and epichlorohydrin are added into a reaction container, and then triamylamine is added into the reaction container under certain conditions. After the reaction is completed, the product is filtered, washed and distilled to obtain epoxypropyl tripentylammonium chloride.

[0024] The reaction temperature is 60-75°C, preferably 60°C.

[0025] The synthesis principle of the invention is as follows: under the condition of alkali catalysis, hydroxypropyl methylcellulose forms hydroxypropyl methylcellulose oxygen anion, and the hydroxypropyl methylcellulose oxygen anion formed after alkali treatment has relatively strong affinity, attacks the carbon atom with fewer substituents of the epoxy group in the epoxypropyl tripentyl ammonium chloride from behind, first forms a relatively weak carbon-oxygen bond with the carbon atom, and at the same time, the carbon-oxygen bond on the epoxy is weakened, and then the CO bond is broken, and the bond between the oxygen anion on the hydroxypropyl methylcellulose and the ring carbon atom is gradually formed to obtain the quaternary ammonium salt type cationic cellulose ether.

[0026] The invention adopts glycidyl tripentylammonium chloride as an etherifying agent, and controls the molar ratio of glycidyl tripentylammonium chloride to hydroxypropyl methylcellulose and the molar ratio of sodium hydroxide to hydroxypropyl methylcellulose, so that the obtained quaternary ammonium salt type cationic cellulose ether has a higher degree of substitution, and the degree of substitution of the obtained quaternary ammonium salt type cationic cellulose ether reaches between 0.45 and 0.65.

[0027] The present invention also provides the use of the quaternary ammonium salt type cationic cellulose ether in preparing a soil conditioner.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] (1) The present invention uses glycidyl tripentylammonium chloride as an etherifying agent, and controls the molar ratio of glycidyl tripentylammonium chloride to hydroxypropyl methylcellulose and the molar ratio of sodium hydroxide to hydroxypropyl methylcellulose to make the obtained quaternary ammonium salt type cationic cellulose ether have a higher degree of substitution, so that the degree of substitution of the obtained quaternary ammonium salt type cationic cellulose ether reaches between 0.45 and 0.65.

[0030] (2) Using the quaternary ammonium salt cationic cellulose ether prepared by the present invention as a component of a soil conditioner for soil improvement can significantly improve the water and fertilizer retention effect of the soil. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a diagram of the soil column leaching experimental device described in the present invention. DETAILED DESCRIPTION

[0032] The above features mentioned in the present invention or the features mentioned in the embodiments can be combined in any way. All the features explained in the specification of this case can be used in combination with any method form, and each feature disclosed in the specification can be replaced by any alternative feature that can provide the same, equal or similar purpose. Therefore, unless otherwise specified, the disclosed features are only general examples of equal or similar features.

[0033] The present invention will be further described below in conjunction with specific examples. These examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In the following examples, the implementation methods for specifying specific conditions are usually based on conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, all percentages and fractions are by weight.

[0034] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those known to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein can be applied to the methods of the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only.

[0035] Basic Example: Preparation of epoxypropyl tripentylammonium chloride

[0036] Potassium sulfate crystals, water, anhydrous ethanol and epichlorohydrin are added into a reaction container, and then triamylamine is added into the reaction container under the condition of 40 ℃. The reaction is carried out for 3 hours at 60 ℃. After the reaction is completed, the product is filtered, washed and distilled to obtain epoxypropyl tripentylammonium chloride.

[0037] Example 1 A cationic polymer

[0038] The cationic polymer is a quaternary ammonium salt type cationic cellulose ether, which is prepared according to the following method:

[0039] (1) adding hydroxypropyl methylcellulose to a reaction device containing a mixed solution of isopropyl alcohol-water-sodium hydroxide (the volume fraction of isopropyl alcohol is 30%), stirring until completely dissolved, and reacting at 40° C. for 1.5 hours to obtain substance A; the molar ratio of sodium hydroxide to hydroxypropyl methylcellulose is 0.30:1;

[0040] (2) Adding glycidyl tripentylammonium chloride (the molar ratio of glycidyl tripentylammonium chloride to hydroxypropyl methylcellulose is 0.35:1) to the substance A obtained in step (1), stirring evenly, reacting at 60° C. for 8 hours, and then precipitating with alcohol after the reaction, and drying at 60° C. for 50 hours to obtain the quaternary ammonium salt cationic cellulose ether.

[0041] Example 2 A cationic polymer

[0042] The cationic polymer is a quaternary ammonium salt type cationic cellulose ether, which is prepared according to the following method:

[0043] (1) adding hydroxypropyl methylcellulose to a reaction device containing a mixed solution of isopropyl alcohol-water-sodium hydroxide (the volume fraction of isopropyl alcohol is 60%), stirring until completely dissolved, and reacting at 50° C. for 0.5 hours to obtain substance A; the molar ratio of sodium hydroxide to hydroxypropyl methylcellulose is 0.5:1;

[0044] (2) Adding glycidyl tripentylammonium chloride (the molar ratio of glycidyl tripentylammonium chloride to hydroxypropyl methylcellulose is 0.65:1) to the substance A obtained in step (1), stirring evenly, reacting at 80° C. for 5 hours, and then precipitating with alcohol after the reaction, and drying at 60° C. for 50 hours to obtain the quaternary ammonium salt cationic cellulose ether.

[0045] Example 3 A cationic polymer

[0046] The cationic polymer is a quaternary ammonium salt type cationic cellulose ether, which is prepared according to the following method:

[0047] (1) adding hydroxypropyl methylcellulose to a reaction device containing a mixed solution of isopropyl alcohol-water-sodium hydroxide (the volume fraction of isopropyl alcohol is 40%), stirring until completely dissolved, and reacting at 45° C. for 1.2 hours to obtain substance A; the molar ratio of sodium hydroxide to hydroxypropyl methylcellulose is 0.45:1;

[0048] (2) Adding glycidyl tripentylammonium chloride (the molar ratio of glycidyl tripentylammonium chloride to hydroxypropyl methylcellulose is 0.45:1) to the substance A obtained in step (1), stirring evenly, reacting at 70° C. for 7 hours, and after the reaction is completed, precipitating with alcohol, and drying at 60° C. for 50 hours to obtain the quaternary ammonium salt type cationic cellulose ether.

[0049] Comparative Example 1

[0050] The difference from Example 3 is that the molar ratio of glycidyl tripentylammonium chloride to hydroxypropyl methylcellulose is 0.25:1, and the rest is the same as Example 3.

[0051] Comparative Example 2

[0052] The difference from Example 3 is that the molar ratio of glycidyl tripentylammonium chloride to hydroxypropyl methylcellulose is 0.8:1, and the rest is the same as Example 3.

[0053] Comparative Example 3

[0054] The difference from Example 3 is that the epoxypropyl tripentylammonium chloride is replaced by epoxypropyl trimethylammonium chloride, and the rest is the same as Example 3.

[0055] Effect test

[0056] 1. Detection of substitution degree of quaternary ammonium salt cationic cellulose ether

[0057] 1.1 Nitrogen content detection

[0058] (1) Catalytic decomposition

[0059] Weigh 1.00g of hydroxypropyl methylcellulose and place it in a 500mL nitrogen determination bottle. Add 10.0g of powdered potassium sulfate and 0.5g of powdered anhydrous copper sulfate. Add 20mL of concentrated sulfuric acid along the bottle wall and wash the powder attached to the bottle wall to the bottom of the flask. Place the flask at a 45-degree angle and heat slowly to keep the solution below the boiling point. In the late stage of sample digestion, the digestion solution is blue-green and clear and transparent. Continue heating for 0.5h.

[0060] (2) Alkalinization distillation

[0061] Cool the solution obtained after nitration to room temperature, slowly add 100 mL of distilled water, shake well, and cool. Slowly add 80 mL of sodium hydroxide solution (300 g / L) along the bottle wall to the bottom of the bottle, slowly add a certain amount of zeolite, use the Kjeldahl nitrogen distillation apparatus to pre-take 50 mL of boric acid solution (20 g / L) and add it to a 250 mL conical flask, heat and distill 2 / 3 of the liquid into the conical flask, and rinse the condenser with water.

[0062] (3) Titration

[0063] Add 10 drops of methyl orange solution to a conical flask and titrate with 0.1 mol / L hydrochloric acid standard solution until the solution changes from orange to red. Nitrogen is released in the form of gas, absorbed by boric acid solution, and then acid-base titrated with hydrochloric acid standard solution titrant to calculate the nitrogen content in the sample.

[0064] (4) Calculation of nitrogen content

[0065] The Kjeldahl method was used to determine the nitrogen content in HPMC. The calculation formula is as follows:

[0066] N={[(V1-V2)·c·14] / m}×100%

[0067] Where:

[0068] N- Nitrogen content of the sample, %;

[0069] V1-the amount of hydrochloric acid standard solution, mL;

[0070] V2-the amount of hydrochloric acid standard solution used in the blank test, mL;

[0071] C-concentration of hydrochloric acid standard solution, mol / L;

[0072] M-sample mass, g;

[0073] 14 = atomic weight of N.

[0074] (5) Calculation of degree of substitution

[0075] The degree of substitution of cationic hydroxypropyl methylcellulose refers to the average number of hydroxyl groups in the basic structural unit of hydroxypropyl methylcellulose molecular weight replaced by substituent groups, that is, the average number of hydroxyl groups in each basic structural unit of hydroxypropyl methylcellulose replaced by the reaction reagent. The calculation formula is:

[0076] DS = (215 × N) / (14-193.5 × N)

[0077] Where:

[0078] DS-degree of substitution;

[0079] 215-average molecular weight of a hydroxypropyl methylcellulose structural unit;

[0080] 193.5-Molecular weight of the structural unit of epoxypropyl tripentylammonium chloride grafted onto hydroxypropyl methylcellulose;

[0081] N-nitrogen content in the product;

[0082] 14- Atomic weight of nitrogen.

[0083] The test results are shown in Table 1 below.

[0084] Table 1

[0085] Degree of substitution Example 1 0.45 Example 2 0.52 Example 3 0.64 Comparative Example 1 0.25 Comparative Example 2 0.38 Comparative Example 3 0.21

[0086] It can be seen from the test results in Table 1 above that the quaternary ammonium salt cationic cellulose ether prepared in the present invention has a higher degree of substitution and has better fertilizer and water retention effects when used for soil improvement.

[0087] 2. Water retention test of quaternary ammonium salt cationic cellulose ether

[0088] In an indoor simulation experiment, air-dried soil passing through a 2 mm sieve was used to test the water retention properties of the quaternary ammonium salt cationic cellulose ether samples prepared in Examples 1-3 and Comparative Examples 1-3.

[0089] Experimental groups: control group: no modifier was added; Example 1-3 groups: quaternary ammonium salt cationic cellulose ether samples prepared in Examples 1-3 were added respectively, with an addition amount of 0.25 g / kg soil; Comparative Example 1-3 groups: quaternary ammonium salt cationic cellulose ether samples prepared in Comparative Examples 1-3 were added respectively, with an addition amount of 0.25 g / kg soil.

[0090] Experimental method: Wrap the bottom of a 6cm diameter PVC pipe with a 200-mesh screen and press it with a bottom cover with holes. Spread a certain amount of quartz sand on the bottom layer inside to prevent soil from flowing out along the seams and affecting the experimental results. Mix 80g of air-dried soil with the quaternary ammonium salt cationic cellulose ether sample and add it to the PVC pipe. Then add 80g of air-dried soil to lay the pipe. Prepare a plastic water frame with a water level not higher than the soil surface. Put the PVC pipe in. Take it out after absorbing water for 24 hours. Let it stand until no water drops. Carefully put it in a 25℃ constant temperature and humidity chamber. Measure the overall weight of the PVC pipe at 1d, 5d and 10d respectively. Repeat the measurement 3 times for each test group, take the average value, and calculate the soil moisture content.

[0091] The test results are shown in Table 2 below.

[0092] Table 2

[0093]

[0094]

[0095] According to the test results in Table 2 above, the quaternary ammonium salt cationic cellulose ether prepared by the present invention has a good water retention effect, the moisture content in the PVC pipe decreases slowly, and the water content in the soil is still above 20% after 10 days. However, changing the mass ratio between the reactants or changing the types of reactants in the comparative example will affect the water retention effect of the quaternary ammonium salt cationic cellulose ether to a certain extent, and accelerate the water loss relative to the example.

[0096] 3. Test of fertilizer retention of quaternary ammonium salt cationic cellulose ether

[0097] Indirect soil column leaching was used to conduct indoor simulation experiments. The fertilizer retention performance of the quaternary ammonium salt cationic cellulose ether samples prepared in Examples 1-3 and Comparative Examples 1-3 was tested using air-dried soil that had passed through a 2 mm sieve.

[0098] Prepare multiple PVC pipes with a height of 30 cm and an inner diameter of 5 cm, seal the bottom with a 120-mesh filter cloth, pad a certain amount of 50-mesh and 120-mesh quartz sand to simulate the tillage layer, and then evenly mix the quaternary ammonium salt cationic cellulose ether sample, fertilizer and soil and put them into the PVC pipe. Experimental grouping: control group: add an equal amount of sterile water; Example 1-3 group: add the quaternary ammonium salt cationic cellulose ether sample prepared in Example 1-3, respectively, with an addition amount of 0.3g / kg soil; Comparative Example 1-3 group: add the quaternary ammonium salt cationic cellulose ether sample prepared in Comparative Example 1-3, respectively, with an addition amount of 0.3g / kg soil. Then cover the top of the soil column with a small amount of 50-mesh quartz sand to prevent water from dripping into the soil layer. Repeat each treatment three times. Each treatment first adds 60mL of water to make the soil moisture close to saturation and stabilize before starting the formal experiment.

[0099] 100 mL of water was added to each treatment group, and the leaching solution was collected at room temperature. After 7 days, 100 mL of water was added for secondary leaching. This was performed four times in total, and the potassium ion content in the leaching solution was measured and recorded to evaluate the fertilizer retention performance of the quaternary ammonium salt cationic cellulose ether. The test results are shown in Table 3 below.

[0100] Table 3

[0101] Potassium ion content (mg) Control group 25.4 Example 1 16.8 Example 2 16.6 Example 3 16.2 Comparative Example 1 18.4 Comparative Example 2 18.0 Comparative Example 3 17.6

[0102] According to the test results in Table 3 above, the quaternary ammonium salt cationic cellulose ether prepared by the present invention has a good fertilizer retention effect, and the content of potassium ions in the eluent is significantly lower than that in the control group, indicating that the quaternary ammonium salt cationic cellulose ether can better adsorb potassium ions, thereby achieving the effect of fertilizer retention. In the comparative example, changing the mass ratio between the reactants or changing the types of reactants will affect the fertilizer retention effect of the quaternary ammonium salt cationic cellulose ether to a certain extent, and accelerate the loss of potassium ions relative to the example.

[0103] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the present invention, but the present invention is not limited thereto. For those skilled in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered as the protection scope of the present invention.

Claims

1. A cationic polymer, wherein the cationic polymer is a quaternary ammonium salt cationic cellulose ether, characterized in that: Prepared as follows: (1) adding hydroxypropyl methylcellulose to a reaction device containing an alkaline isopropanol solution, stirring until completely dissolved, and obtaining substance A after reaction; (2) adding glycidyltriammonium chloride to the substance A obtained in step (1), stirring the mixture evenly and reacting the mixture; after the reaction is completed, purifying and drying the mixture to obtain the quaternary ammonium salt type cationic cellulose ether.

2. The cationic polymer according to claim 1, characterized in that: The alkaline isopropanol solution described in step (1) is a mixed solution of isopropanol-water-sodium hydroxide; the volume fraction of the isopropanol is 30-60%.

3. The cationic polymer according to claim 1, characterized in that: The molar ratio of the sodium hydroxide to the hydroxypropyl methylcellulose is 0.30-0.50:

1.

4. The cationic polymer according to claim 1, characterized in that: Step (1) needs to be carried out under heating conditions, the heating temperature is 40-50° C., and the reaction time is 0.5-1.5 hours.

5. The cationic polymer according to claim 1, characterized in that: The molar ratio of glycidyl tripentylammonium chloride to hydroxypropyl methylcellulose described in step (2) is 0.35-0.65:

1.

6. The cationic polymer according to claim 5, characterized in that: The molar ratio of glycidyltripentyl ammonium chloride to hydroxypropyl methylcellulose described in step (2) is 0.45:

1.

7. The cationic polymer according to claim 1, characterized in that: The reaction temperature in step (2) is 60-80° C. and the reaction time is 5-8 hours.

8. The cationic polymer according to claim 7, characterized in that: The reaction temperature in step (2) is 70° C. and the reaction time is 7 hours.

9. The cationic polymer according to claim 1, characterized in that: The substitution degree of the quaternary ammonium salt type cationic cellulose ether is between 0.45 and 0.

65.

10. Use of the quaternary ammonium salt cationic cellulose ether according to any one of claims 1 to 9 in the preparation of a soil conditioner.